Comparison of three sampling procedures for evaluating intestinal villi: A swine model¤ - Itza, Mateo Fabian (2018)
Background: Villi morphology and function affect the absorption capacity of the small intestine. Most tissues are fragile and their morphology may change with excessive manipulation and inadequate sampling techniques. Intestinal sampling includes methodologies such as cutting longitudinally or transversely, keeping the intestinal content in it and preserving all in a 10% formalin solution; washing the intestinal sample in saline solution while emptying it by pressing downwards with two fingers, conserving the sample in a 10% formalin solution and knotting both ends of the sample, introducing 10% formalin into it and preserving it in the same solution. Objective: To compare height, area and desquamation caused by washing, pressing, and knotting used in sampling and conservation techniques of small intestine villi of pigs. Methods: Samples (n = 270) from duodenum, jejunum and ileum of 30 Landrace × Yorkshire crossed pigs, aged 7 to 8 months were randomly subjected to washing, soft pressing or knotting procedures, fixed in 10% formalin solution, embedded in paraffin, and stained with eosin and hematoxylin. Intestinal villi in each slide were observed to determine height, surface area and cellular desquamation of each villus. Results: Villi height from duodenum and ileum knotted samples was higher (p<0.05) compared with samples from the other procedures in the same anatomical portion, which were similar to each other (p>0.05). Villi from knotted jejunum samples were the shortest (p<0.05) compared to the other two procedures, which were similar to each other (p>0.05). Knotted samples from ileum had larger villi area compared with the rest of the procedures and intestinal portions (p<0.05). Villi desquamation was similar among procedures and portions of the intestine (p>0.05). Conclusion: Knotting is the recommended procedure for intestinal cell morphometry evaluation, as values of villi height and area are higher. Desquamation in the three procedures may be related to epithelial restoration processes.